1998
DOI: 10.1128/aem.64.8.3063-3065.1998
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Response in the Thermophilic Enteric Yeast Arxiozyma telluris

Abstract: Heat stress tolerance was examined in the thermophilic enteric yeast Arxiozyma telluris. Heat shock acquisition of thermotolerance and synthesis of heat shock proteins hsp 104, hsp 90, hsp 70, and hsp 60 were induced by a mild heat shock at temperatures from 35 to 40°C for 30 min. The results demonstrate that a yeast which occupies a specialized ecological niche exhibits a typical heat shock response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They observed that when the yeast Saccharomyces cerevisiae grown at 23–25°C was shifted to 36–37°C, it provided dramatic protection to lethal temperatures in comparison with untreated cells. Deegenaars and Watson (1998) observed that the yeast Arxiozyma telluris was also able to show a heat‐shock response and Ananta and Knorr (2003) demonstrated thermotolerance acquisition by previous temperature treatments on Lactobacillus GG at temperatures slightly higher at their optimal growth temperature. Thus, these results suggest that the application of a mild heat treatment does lead to protection of C. sake CPA‐1 cells from death during subsequent more extreme heat exposure.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that when the yeast Saccharomyces cerevisiae grown at 23–25°C was shifted to 36–37°C, it provided dramatic protection to lethal temperatures in comparison with untreated cells. Deegenaars and Watson (1998) observed that the yeast Arxiozyma telluris was also able to show a heat‐shock response and Ananta and Knorr (2003) demonstrated thermotolerance acquisition by previous temperature treatments on Lactobacillus GG at temperatures slightly higher at their optimal growth temperature. Thus, these results suggest that the application of a mild heat treatment does lead to protection of C. sake CPA‐1 cells from death during subsequent more extreme heat exposure.…”
Section: Discussionmentioning
confidence: 99%